2008
DOI: 10.1677/jme-08-0149
|View full text |Cite
|
Sign up to set email alerts
|

No evidence for a bone phenotype in GPRC6A knockout mice under normal physiological conditions

Abstract: GPRC6A is a seven-transmembrane receptor mediating signaling by a wide range of L-a-amino acids, a signaling augmented by the divalent cations Ca 2C and Mg 2C . GPRC6A transcripts are detected in numerous mammalian tissues, but the physiological role of the receptor is thus far elusive. Analogously to the closely related calcium-sensing receptor, GPRC6A has been proposed to function as a metabolic sensor of Ca 2C and amino acids in bone and other tissues. In the present study, we have generated the first GPRC6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 58 publications
4
58
1
Order By: Relevance
“…(30) Other studies have suggested the presence of an alternate calcium receptor in bone, GPRC6A, that might be involved in skeletal mineralization, (31,32) although conflicting reports on the skeletal phenotype of GPRC6A null mice have been published recently. (32,33) Our results cannot exclude the possibility that other receptor mechanisms or nonreceptor mechanisms are involved in mineralization of bone via increased [Ca 2þ ] e .…”
Section: Discussionmentioning
confidence: 74%
“…(30) Other studies have suggested the presence of an alternate calcium receptor in bone, GPRC6A, that might be involved in skeletal mineralization, (31,32) although conflicting reports on the skeletal phenotype of GPRC6A null mice have been published recently. (32,33) Our results cannot exclude the possibility that other receptor mechanisms or nonreceptor mechanisms are involved in mineralization of bone via increased [Ca 2þ ] e .…”
Section: Discussionmentioning
confidence: 74%
“…This restricted pattern of expression in gonads may explain why osteocalcin can increase testosterone production from testis, but not from ovaries. The investigation of the role of Gprc6a in regulation of bone mass accrual has generated contradicting findings (Pi et al 2008, Wellendorph et al 2009, and thus this aspect of Gprc6a function will not be developed further in this review.…”
Section: Osteocalcin Acts On Leydig Cells Through Its Receptor Gprc6amentioning
confidence: 99%
“…A promiscuous range of nonselective ligands and a broad but low-level expression profile have complicated elucidation of the physiologic function of this receptor. Based on studies in GPRC6A knockout mice, the receptor is now suggested to be involved in inflammatory, metabolic, and endocrine regulation; however, the specific role of GPRC6A is still unknown (Pi et al, 2008(Pi et al, , 2011Wellendorph et al, 2009;Rossol et al, 2012;Smajilovic et al, 2013;Clemmensen et al, 2013a,b).…”
Section: Introductionmentioning
confidence: 99%